Frequency and Risk Factors for Additional Lesions in the Axial Spine in Subjects With Chordoma: Indications for Screening. Issue 1 (1st January 2017) - Sebro, Ronnie; DeLaney, Thomas F.; Hornicek, Francis; Schwab, Joseph; Choy, Edwin; Nielsen, G. Petur; Rosenthal, Daniel I.
Abstract : Study Design: Retrospective cohort study. Objective: We aim to evaluate the frequency and clinical significance of additional lesions in the axial spine in subjects with chordoma and to assess the need for screening. Summary of Background Data: Chordomas are rare tumors that may be multicentric or metastasize and affect several bones in the axial spine. The incidence of multiple lesions in the axial spine is unknown. Understanding the incidence rate of multiple lesions in the spine in subjects with chordomas will help guide utilization of total spine screening imaging. Methods: We performed a retrospective review of medical records of 42 subjects with histologically confirmed chordomas who had complete imaging of the axial spine. Lesions with imaging characteristics suggestive of chordomas/notochordal remnants were identified. Data on age at diagnosis, sex, size (in maximal dimension), type of chordoma (conventional, chondroid, or dedifferentiated), and whether pulmonary metastases were present were recorded. Binomial two-sample tests of proportions were used to compare proportions. Logistic regression was used to assess predictors of additional lesions. Results: Forty-two subjects (57.1% male) were identified. The proportion of subjects with additional lesions in the axial spine was 16.7% (7/42). Age, sex, size, and subtype of chordoma were not significant predictors of having additional lesions ( P  > 0.05 for each variable). However, having pulmonary metastases was a significant predictor of having additional lesions ( P  < 0.05). Conclusion: Approximately 17% of subjects with chordomas had additional lesions in the axial spine. It is unclear whether these represent metastases, synchronous primary chordomas or notochordal remnant tissue. Screening imaging of the axial spine may reveal additional lesions in particular in subjects with pulmonary metastases. Level of Evidence: 3